2016
DOI: 10.4103/0366-6999.193461
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel Drug-eluting Tracheal Stent Could Reduce Granulation Tissue Formation in a Canine Model

Abstract: Background:Currently available silicone and metallic stents for tracheal stenosis are associated with many problems. Granulation proliferation is one of the main complications. The present study aimed to evaluate the efficacy of paclitaxel drug-eluting tracheal stent in reducing granulation tissue formation in a canine model, as well as the pharmacokinetic features and safety profiles of the coated drug.Methods:Eight beagles were randomly divided into a control group (bare-metal stent group, n = 4) and an expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 24 publications
2
39
0
Order By: Relevance
“…This is the first time, to our knowledge, a PLLA-PCL tracheal stent was deployed in a mouse model. Although other materials were used in studies with rabbit and canine models [26,27,28] , PLLA-PCL chosen for this study because it causes little inflammation in the native tissue [29] . Moreover, the rabbit and canine models used in the past do not use the LTS disease model to test the effects of a DES.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first time, to our knowledge, a PLLA-PCL tracheal stent was deployed in a mouse model. Although other materials were used in studies with rabbit and canine models [26,27,28] , PLLA-PCL chosen for this study because it causes little inflammation in the native tissue [29] . Moreover, the rabbit and canine models used in the past do not use the LTS disease model to test the effects of a DES.…”
Section: Discussionmentioning
confidence: 99%
“…This delivery system, which combines a stent with a gelatin gel, can be modified easily and could be used to deliver other substances at high local concentrations to the tissues surrounding the stent. One potential application could be the delivery of agents that affect granulation tissue formation, for example mitomycin [37-43], which might be useful in preventing the buildup of granulation tissue. This strategy could also be used to deliver compounds that stimulate the immune response against malignant tumors infiltrating the airways [16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that PTX, an antineoplastic agent, could reduce the development of PC and subsequent bile duct stricture. [ 14 15 ] Unfortunately, poor solubility has limited its clinical usage. [ 16 ] In the last few years, great efforts have been made for development of new delivery systems for PTX, such as polymer conjugates, liposomes, polymeric micelles, parenteral emulsions, polymeric micro/nanoparticles, and water-soluble prodrugs.…”
Section: Discussionmentioning
confidence: 99%